2018
DOI: 10.1021/acs.jpcc.8b08641
|View full text |Cite
|
Sign up to set email alerts
|

Role of TiO2 Anatase Surface Morphology on Organophosphorus Interfacial Chemistry

Abstract: Optimization of physicochemical properties of TiO 2 anatase for organophosphorus remediation remains challenging. One approach is to use anatase nanofibers, prepared from hydrothermally synthesized titanates. Charge densities and potentials of anatase nanofibers were determined from atomic force microscopy force−curve measurements using the modified Derjaguin, Landau, Verwey, Overbeek theory, which includes roughness and hydration forces, in the pH range 4−9. Calculated values were −0.007 to −0.03 C m −2 and −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The ζ-potential measurements (Figure 5) show that the bare TiO 2 has a Point of Zero Charge (PZC) of 3.6, that is, a value lower than usual for TiO 2 : for instance, Degussa P25 (with particle size between 20 and 40 nm) has a PZC around 6.2–6.9 [43,44]; for pure TiO 2 NPs (with diameter in the range of 14–33 nm), a PZC of 6.8 [45] was reported; Allard et al found a PZC of 6.1 with commercial anatase NPs (with a diameter of ca. 20 nm) [46]; Al-Hetlani et al found a PZC of 5.98 for smaller anatase NPs (around 7.2 nm [47]); and Huijun et al reported a PZC of 6.2 for anatase NPs (5–10 nm) [48]. The much lower value of PZC reported here may be ascribed, rather than to the size of TiO 2 NPs, to the type of synthesis [49,50] that probably favors the formation of a very acidic surface, in agreement with previous work [43].…”
Section: Resultsmentioning
confidence: 99%
“…The ζ-potential measurements (Figure 5) show that the bare TiO 2 has a Point of Zero Charge (PZC) of 3.6, that is, a value lower than usual for TiO 2 : for instance, Degussa P25 (with particle size between 20 and 40 nm) has a PZC around 6.2–6.9 [43,44]; for pure TiO 2 NPs (with diameter in the range of 14–33 nm), a PZC of 6.8 [45] was reported; Allard et al found a PZC of 6.1 with commercial anatase NPs (with a diameter of ca. 20 nm) [46]; Al-Hetlani et al found a PZC of 5.98 for smaller anatase NPs (around 7.2 nm [47]); and Huijun et al reported a PZC of 6.2 for anatase NPs (5–10 nm) [48]. The much lower value of PZC reported here may be ascribed, rather than to the size of TiO 2 NPs, to the type of synthesis [49,50] that probably favors the formation of a very acidic surface, in agreement with previous work [43].…”
Section: Resultsmentioning
confidence: 99%
“…The topological analysis of the charge density distibution was performed by the Bader’s quantum theory of atoms in molecules [ 54 ] by using AIMALL software (version 17.01.25) [ 55 ]. The (TiO 2 ) 10 nanocluster was used as a model for all possible molecular implant surface/alendronate interaction predictions [ 56 , 57 ]. Detail description of the modeling, as well as results ( Tables S1–S4 ), are given in Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…The experimental findings were corroborated by means of DFT calculations based on effects of cholecalciferol (D3 vitamin) as well as glycerol as its alcoholic solvent in pharmaceutical composition of vitamin D3 solution. The small (TiO 2 ) 10 nanocluster served as a credible model for all possible molecular Ti-implant surface/bioactive molecule interaction predictions [26,27]. There is a possibility that the presence of other kinds of Ti-implant surface/molecule interactions (due to the presence of glycerol solvent) except the (TiO 2 ) 10 -cholecalciferol interaction could be responsible for influencing the coating formation mechanism.…”
Section: Formation Mechanism Of Bioactive Implant Coatingmentioning
confidence: 98%
“…All calculations were performed by means of quantum chemical calculations at the density functional theory (DFT) level using the Gaussian 09 program (revision D1) [25]. The small (TiO 2 ) 10 nanocluster served as a credible model for all possible molecular surface/bioactive molecule interaction predictions [26,27]. The M06 functional designed by Truhlar's group was selected [28][29][30].…”
Section: Computational Detailsmentioning
confidence: 99%